Users' and health service providers' perception on quality of laboratory malaria diagnosis in Tanzania - Massaga Julius J; Tenu Filemoni; Rwegoshora Rwehumbiza T; Ishengoma Deus RS; Derua Yahya A; Mboera Leonard EG; Magesa Stephen M (Malaria Journal, 2011)
Abstract Background Correct diagnosis of malaria is crucial for proper treatment of patients and surveillance of the disease. However, laboratory diagnosis of malaria in Tanzania is constrained by inadequate infrastructure, consumables and insufficient skilled personnel. Furthermore, the perceptions and attitude of health service providers (laboratory personnel and clinicians) and users (patients/care-takers) on the quality of laboratory services also present a significant challenge in the utilization of the available services. This study was conducted to assess perceptions of users and health-care providers on the quality and utilization of laboratory malaria diagnostic services in six districts from three regions in Tanzania. Methods Questionnaires were used to collect information from laboratory personnel, clinicians and patients or care-takers. Results A total of 63 laboratory personnel, 61 clinicians and 753 patients/care-takers were interviewed. Forty-six (73%) laboratory personnel claimed to be overworked, poorly motivated and that their laboratories were under-equipped. About 19% (N = 12) of the laboratory personnel were lacking professional qualification. Thirty-seven clinicians (60.7%) always requested for blood smear examination to confirm malaria. Only twenty five (41.0%) clinicians considered malaria microscopy results from their respective laboratories to be reliable. Forty-five (73.8%) clinicians reported to have been satisfied with malaria diagnostic services provided by their respective laboratories. Majority (90.2%, N = 679) of the patients or care-takers were satisfied with the laboratory services. Conclusion The findings show that laboratory personnel were not satisfied with the prevailing working conditions, which were reported to undermine laboratory performance. It was evident that there was no standard criteria for ordering malaria laboratory tests and test results were under-utilized. Majority of the clinicians and patients or care-takers were comfortable with the overall performance of laboratories, but laboratory results were having less impact on patient management.